ANALISIS UPAYA DAN PENANGANAN PEMBIAYAAN NASABAH YANG WAFAT SESUDAH JATUH TEMPO (STUDI KASUS DI PT BPRS RIYAL IRSYADI BEKASI) - Anto Apriyanto; Julianna Rai Hakim Isnaini (Institut Bisnis Muhammadiyah Bekasi, 2022)
Islamic banking, as is the case with conventional banking in Indonesia, is an intermediary institution whose function is to collect funds and distribute funds to the public in the form of financing facilities. In this case, the author is interested in examining the analysis of efforts and handling of financing on customers who died after the maturity of the study at BPRS Riyal Irsyadi Bekasi. Based on this fact, the author is interested in conducting research by formulating the following problem: how to settle the financing whose customer dies after maturity (there is still an obligation to pay installments) at BPRS Riyal Irsyadi. The purpose of this research is to find out the settlement of financing for customers who die or die after maturity. To solve the existing problems the author uses a type of field research using a descriptive qualitative approach. The data collection method that the writer uses is the interview and observation method. The results of the settlement research carried out for the case of customers who died or died by way of heirs who paid or continued the financing installments at Riyal Irsyadi's BPRS.